Localized Deformation in Compression and Folding of Paperboard. Issue 7 (3rd May 2016) - Borgqvist, Eric; Wallin, Mathias; Tryding, Johan; Ristinmaa, Matti; Tudisco, Erika
Abstract : The localized deformation patterns developed during in‐plane compression and folding of paperboard have been studied in this work. X‐ray post‐mortem images reveal that cellulose fibres have been reoriented along localized bands in both the compression and folding tests. In folding, the paperboard typically fails on the side where the compressive stresses exists and wrinkles are formed. The in‐plane compression test is however difficult to perform because of the slender geometry of the paperboard. A common technique to determine the compression strength is to use the so‐called short‐span compression test (SCT). In the SCT, a paperboard with a free length of 0.7 mm is compressed. Another technique to measure the compression strength is the long edge test where the motion of the paperboard is constrained on the top and bottom to prevent buckling. A continuum model that previously has been proposed by the authors is further developed and utilized to predict the occurrence of the localized bands. It is shown that the in‐plane strength in compression for paperboard can be correlated to the mechanical behaviour in folding. By tuning the in‐plane yield parameters to the SCT response, it is shown that the global response in folding can be predicted. The simulations are able to predict the formation of wrinkles, and the deformation field is in agreement with the measured deformation pattern. The model predicts an unstable material response associated with localized deformation into bands in both the SCT and folding. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A novel approach to simulate and study the short‐span compression test and folding of paperboard is presented. A specific material model is used to predict the localized deformation observed from x‐ray tomograph images.